Issues & Challenges of Merger & Acquisition for Indian Companies in the Global Market - Navendu Vijayvergia; Poorvi Agrawal (The Bioscan, 2025)
Mergers and Acquisitions (M&A) are critical growth strategies for Indian companies seeking to expand their global footprint. However, these transactions are inherently complex and present numerous challenges that can significantly impact their success. This research paper examines the key issues and challenges Indian companies face during M&A processes in the global market. Among the most pressing concerns are cultural integration, alignment of business strategies, regulatory hurdles, and managing employee morale and retention. Additionally, the complexities of cross-border legal frameworks and due diligence processes can pose significant barriers. The paper emphasizes the importance of strategic alignment, effective communication, thorough due diligence, and post-merger integration planning as critical factors for successful M&A outcomes. By analyzing landmark cases of M&A in India, the paper provides insights into best practices for navigating these challenges, ultimately offering a roadmap for Indian companies to enhance the effectiveness of their global M&A transactions. Through careful preparation and execution, companies can mitigate risks, capitalize on synergies, and realize the full potential of M&A deals.